The Effect Of Health Service On Patient Satisfaction In Haji Hospital, Medan City - Andani, Nidya; Nyorong, Mappeaty; ., Asriwati (British Journal of Healthcare and Medical Research, 2021)
The study aimed to determine the effect of quality and the dominant variables affecting service on patient satisfaction at the Haji Hospital-Medan in 2020. Quantitative research was conducted through a survey analytic research approach with a cross sectional study approach. Test through logistic regression on independent variables, namely; Reliability, Responsiveness, Assurance, Empathy and Tangible from the questionnaire data of respondents as many as 80 samples. The results showed that there was a significant effect of service quality on patient satisfaction from four variables, namely; the reliability of the p value is 0.000 (p <0.05), the responsiveness of the p value is 0.038 (p <0.05), the empathy p value is 0.016 (p <0.05), the tangible p value is 0.001 (p <0.05). The assurance variable, there is no effect of the quality of health services on patient satisfaction with a p value of 0.696 (p> 0.05). The dominant variable affecting patient satisfaction is the variable of empathy with an odds ratio of 0.2120.